Viabilidade técnica, econômica e social do aproveitamento das águas de chuva e cinzas para consumo não potável na cidade de Santa Maria/RS - Pozzebon, Pedro Henrique Bürger (2013)
The objective of this work was to study a technical, social and economical viability of the optimization for grey and rain waters for non drinkable consumption in the city of Santa Maria, RS. The volume of the rain water tank was dimensioned in 15 m³, and so, guaranteeing the water supply in 33,55%. The rain water tank mixed with grey waters was dimensioned in 2.12m³, providing 100% of demand. Rain water optimization system provides an economy of R$ 937,19/a year, and the value of its investment was estimated in R$ 8.078,34, with maintenance and operation cost of R$ 150,00/a year. Its present net value ranged from R$ 5.629,61 to R$ 7.665,49; the payback was from ten years and three months to eleven years and four months; the internal rate of return was between 7,41% and 5,97%, and the relation cost/benefit was from 1,49 to 1,66. The mixture system of rain and grey waters saves R$ 2.793,42/a year, and the investment value was estimated in R$ 25.384,33, with operation and maintenance cost of R$ 301,74/a year. Its present net value ranged from R$ 18.679,38 to R$ 24.449,23. Payback was from ten years and two months to ten years and eleven months; the internal rate of return (IRR) was between 7,51 and 6,22; and the relation cost/benefit was between 1,58 and 1,78. In relation to social viability, a survey with people from 200 homes was accomplished to verify knowledge and acceptance of those systems population. Both, rain and grey waters optimization studies have demonstrated to be technically, economically, and socially viable.